2015
DOI: 10.12974/2311-858x.2015.03.01.4
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacognostical Standardization and High Performance Thin Layer Chromatography (HPTLC) of Root of Saccharum officinarum Linn. (Poaceae)

Abstract: The purpose of the present study is to investigate the pharmacognostical characteristics of the roots of Saccharum officinarum Linn. (poaceae) to establish standardized parameters. Macroscopic, microscopic, and physicochemical evaluation; preliminary phytochemical analyses and high performance thin layer chromatography (HPTLC) profile were done for qualitative phytochemical evaluation. Roots are grey to blackish brown, fibrous, solid, jointed, odour and taste not distinct. Transverse section of both thin and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…31 Jayalakshmi et al . 32 and Khaerunnisa et al 33 reported the presence of flavonoids as a secondary metabolite found in reed root extract using water or alcohol solvents. Dhianawaty et al 34 reported that from 96 mg of alcoholic extract of the roots of the reeds, the flavonoid content was found to be 1.17%.…”
Section: Effects Of I Cylindrica Root Ethanol Extract On Serum Testos...mentioning
confidence: 99%
“…31 Jayalakshmi et al . 32 and Khaerunnisa et al 33 reported the presence of flavonoids as a secondary metabolite found in reed root extract using water or alcohol solvents. Dhianawaty et al 34 reported that from 96 mg of alcoholic extract of the roots of the reeds, the flavonoid content was found to be 1.17%.…”
Section: Effects Of I Cylindrica Root Ethanol Extract On Serum Testos...mentioning
confidence: 99%